Analysis of Operational and Maintenance Performance of Cimedang - Ciputrapinggan Service Unit (SUP) Merjan Irrigation Area Pangandaran Regency - Muhammad Ikhsan Yusuf; Nurdiyanto Nurdiyanto (Journal of World Science, 2025)
Water is a natural resource that is very important for the continuity of human life. Human needs for water include drinking, cooking, farming, washing, and so on. The Cimedang-Ciputrapangan service unit (SUP) has a very strategic role because this officer has the authority to regulate and distribute water to agricultural land. While the amount of water supply from upstream sometimes does not cover the needs of the work area, the ability to process and operate the irrigation network is very important to ensure that irrigation water can be distributed. The purpose of the Merjan DI Operation and Maintenance Performance Analysis is to provide useful input or information and provide an overview and solutions to problems that occur at the irrigation network level. The method utilized is qualitative, focusing on in-depth communication; however, it lacks specific details regarding data collection and analysis techniques. The analysis reveals that, despite an effective irrigation network, there is an 84% staffing shortage among the management personnel, indicating a significant need for improvement in operational capacity. The research findings are clearly stated, outlining the condition of the irrigation network and its ability to meet rainfall and irrigation needs.